Three-Dimensional Geometric Morphometry of Facial Soft Tissue Changes After Bilateral Sagittal Split Ramus Osteotomy. Issue 1 (7th January 2022) - Al Bougha, Safieh; Nakano, Hiroyuki; Yasuda, Kousuke; Suzuki, Kei; Yamada, Tomohiro; Takahashi, Ichiro; Ueno, Takaaki; Mori, Yoshihide
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This study aimed to evaluate the performance of geometric morphometry (GM) to assess the changes in facial soft tissue after orthognathic surgery. Subjects were 27 patients (skeletal class III) who underwent bilateral sagittal split ramus osteotomy and 27 volunteers as a control group. Computed tomography images of each patient were obtained before surgery (T0) and 6 months after surgery (T1). Computed tomography images of 27 volunteers (skeletal class I) were also obtained as a control group. Using a three-dimensional (3D) modeling software, 3D models were created and exported to a 3D surface analyzing software for geometric morphometry and principal component (PC) analysis. Significant differences in facial soft tissue were found in the first and second of 15 PC. The first PC represented variation in the lower facial height, and the second PC represented variation in the anterior-posterior position of the chin. Comparing the pre- and post-operative images, they illustrated that lower facial height was decreased, and the chin and lower lip moved posteriorly. Geometric morphometry showed to be a successful tool to isolate surgery-related changes from interindividual morphological variations.